The ability of the YAS and AR CALUX assays to detect the additive effects of anti-androgenic fungicide mixtures. (22nd January 2016) - Seeger, Bettina; Klawonn, Frank; Bekale, Boris Nguema; Steinberg, Pablo
Highlights: Evaluation of iso-effective binary and ternary mixtures of anti-androgenic pesticides. Additive anti-androgenic effects of fungicide mixtures in AR CALUX and YAS. Transferability to human exposure scenario discussed. Hormonally active pesticide and contaminant mixtures should be cumulatively assessed. Abstract: Actual risk assessment only takes single pesticides into account, although about one third of the analyzed food samples in the European Union was contaminated with pesticide mixtures in 2013. A cumulative approach would group pesticides that share the same mechanism of toxicity. We evaluated the combination effects of low effect concentrations of binary and ternary mixtures of six anti-androgenic fungicides (procymidone, vinclozolin, tebuconazole, propiconazole, fenarimol and prochloraz) antagonizing the human androgen receptor (hAR) in the Yeast-based Androgen Screen assay (YAS) as well as in the AR Chemical-Activated LUciferase gene eXpression (AR CALUX) assay by means of concentration addition and nonlinear regression. The mixture effects were essentially additive when the fungicides were applied as iso-effective low inhibitory concentration combinations, independently from the used assay and as shown by the excellent agreement between experimental and predicted data. Both assays were successfully applied to evaluate the additive effects of fungicide mixtures at low concentrations. Since pesticide residues occur in/on foodstuffs in the EU at rather low concentrations and hormonally active environmental contaminants may concomitantly be present, more complex mixtures of anti-androgenic chemicals, not only pesticides, should be tested in the future when wanting to apply a target organ-based risk assessment approach.